A possibilidade da constituição de um direito internacional público: inter-relação entre filosofia do direito e da história a propósito da crítica de Hegel à Kant - AMORIM FILHO, Luis Carlos Serra (2025)
Public law is a field of law that deals with matters related to pacts, laws, treaties, and negotiations between countries and institutions. History, on the other hand, is the science that deals with human actions in time. Both fields had their origins in Ancient Greece and have been, and still are, widely discussed by philosophy. This research proposes to discuss the meeting point between these two areas in an interdisciplinary way, specifically in the modern period, through the Philosophy of History. The Philosophy of History is considered an area of philosophy that seeks to interpret historical events through philosophical analysis. In this context, while historians focus on narrating human actions over time, philosophers seek to find the meaning or purpose (télos) behind history. During the Enlightenment, Kant entered this historical-philosophical debate, postulating the existence of progress in which human beings follow a “secret plan of nature” to fulfill their natural dispositions. This is an idea of reason that has a theoretical-practical function, directing understanding to interpret human relationships in accordance with purposes, including the cosmopolitan purpose. Later, Hegel expanded this discussion, presenting not only a notion of the development of human actions as progress in the consciousness of freedom, but also the idea that humanity seeks to achieve this consciousness. For Hegel, there is a reason governing the world, and history has a meaning that is not just an idea of reason, but a fact that can be demonstrated and recognized by speculative knowledge, that is, philosophy. According to him, the end of progress would be achieved by the Germanic people in the 19th century, through their notion of State. Unlike Kant, Hegel postulates that the “end of history” would be a State that regulated law, and not cosmopolitanism. Thus, this research's main objective is to investigate the relationship between public law and history based on Hegel's criticism of the Kantian project of Perpetual Peace. The methodological path followed was a bibliographic study of a basic nature, with a qualitative approach. The results obtained so far show that, when dealing with the same object — history —, Kant and Hegel follow similar paths. Firstly, both establish the epistemic limits of history and what philosophy adds to this investigation. In the same way, both defend a continuous progress in history, which can be seen in Morals for Kant and Ethics for Hegel. Even though they use different terms, the background is the same: both are talking about freedom from a civil point of view. However, when it comes to achieving complete freedom, Kant and Hegel present antagonistic thoughts. Kant argues that humanity will gradually realize its provisions, through the establishment of a society mediated by external laws, which allows the coexistence of freedoms, which means the institution of public law to resolve internal and external conflicts, aiming at cosmopolitanism. Hegel believes that freedom is achieved through the development of human consciousness and the self-recognition of individuals as part of a whole, which is viable through a State that guarantees individual and collective rights, including internal and external security, in exchange for compliance duties for everyone. Hegel criticizes Kant for conceiving cosmopolitanism and perpetual peace as goals to be achieved through a universal pact among nations. For Hegel, this Kantian approach was abstract, as it disregarded the concrete realities of history and the centrality of the state as the means for realizing freedom. He argued that, according to the law of nations, states should respect each other, but war, though undesirable, was seen as a legitimate possibility within the historical dynamic.